STABILITY OF CYLINDRICAL SHELLS - Todchuk, Volodymyr (Proceedings of National Aviation University (archive), 2018)
Purpose: Obtain more precise formulas for the theoretical axial critical load of a hinged cylindrical shell; find the cause of large differences between calculated and experimental critical loads. Methods: The energy criterion of stability and the relations of the general linear theory of thin-walled shells are used. Results: New formulas for the dependence of the critical load on the mechanical and geometric characteristics of the shell and the parameters of wave formation are obtained. The values ​​of the critical loads calculated from these formulas are close to the experimental data. A greater dependence of critical loads on: the ratio of the radius to the thickness of the shell is revealed; the ratio of length to radius; boundary conditions. Discussion: Cylindrical shells are widely used in engineering structures. The loss of stability of the shell can lead to the destruction of the structure. To estimate the bearing capacity of engineering structures, exact formulas are needed to calculate the critical loads of shells under axial compression. Such formulas have not yet been obtained. The reason for the large discrepancies between the theoretical and experimental values ​​of the axial critical loads of cylindrical shells was not found. In this paper, an attempt is made to solve this problem. In contrast to the conventional approach, it is assumed here that when the shell is buckled, the distance between its ends does not change. This approach allowed obtaining formulas of axial critical loads that more accurately describe the process of loss of stability of a cylindrical shell under axial compression. Analysis of the obtained results allows us to conclude that the obtained formulas can be used for real calculations of critical loads of cylindrical shells, and the proposed approach can be used to continue studies of the stability of thin-walled structures.